2000
DOI: 10.1097/00002800-200007000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Clinical Credibility as a Nurse Teacher in a Postgraduate Tertiary Specialization Program

Abstract: This paper addresses the issues surrounding clinical credibility and describes how a Hong Kong specialist nurse teacher maintains clinical credibility. The aim is to explore the credibility of the nurse teacher in relation to the clinical knowledge and skills that will enhance postgraduate students' clinical scholarship. The paper describes a model for maintaining specialist teachers' clinical credibility and innovative strategies to achieve this goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For instance, applicants with a minimum of clinical work experience should be selected when recruiting nursing lecturers and instructors. According to Nahas, an instructor should have at least 5 years of experience in clinical practice, be able to express their experiences to students, educate using new approaches such as role-playing, and ultimately provide an environment for better learning to be able to function properly using such approaches [12] . Ousey stated that lecturers are considered as a source of support for teaching and internships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, applicants with a minimum of clinical work experience should be selected when recruiting nursing lecturers and instructors. According to Nahas, an instructor should have at least 5 years of experience in clinical practice, be able to express their experiences to students, educate using new approaches such as role-playing, and ultimately provide an environment for better learning to be able to function properly using such approaches [12] . Ousey stated that lecturers are considered as a source of support for teaching and internships.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the ndings obtained from the reviewed studies, it can be concluded that clinical credibility of nursing lecturers is more related to the practical experience and skills of instructors. Therefore, strategies should be adopted to improve or maintain the clinical credibility of the lecturers [11,12] . Various studies have addressed and explored strategies for maintaining and improving clinical credibility based on the experiences of clinical instructors, and conducting a review study can integrate results of such studies.…”
Section: Introductionmentioning
confidence: 99%
“…There is a dearth of research regarding the role of faculty and expectations of clinical competency. Nahas described nursing education in cosmopolitan Hong Kong noting that nursing faculty, as in Pakistan, are not responsible for clinical supervision of students 1 . However, she advocated nursing faculty maintaining clinical credibility, or competence, as faculty are accountable for students’ learning regardless of the classroom or clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest that many in the nursing profession believe that nurse educators must work in clinical practice in order to be clinically credible (Aston, Mallik, Day, & Fraser, 2000;Goorapah, 1997;Nahas, 2000). Calpin- suggests that rather than saying nurse educators are totally removed from the practice or patient-centred world they should be considered as having a person-centred perspective where their area of specialisation and expertise is with student nurses.…”
Section: Clinical Credibilitymentioning
confidence: 99%